Analisis Implementasi Coretax dalam Administrasi Perpajakan pada BBPMB tekMIRA Kota Bandung Melalui Pendekatan Technology Acceptance Model - Nadila Putri Aulia; Evi Sofyati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The implementation of good governance is an important aspect in supporting accountability, transparency, and effectiveness in public sector organizations. In tax administration, the application of an integrated administrative system is expected to support the implementation of good governance principles. The Coretax Administration System was implemented as an integrated tax administration system; however, its implementation still faces technical challenges and requires user adaptation. This study aims to analyze the implementation of Coretax in tax administration at the Balai Besar Pengujian Mineral dan Batubara (BBPMB) tekMIRA Bandung through the Technology Acceptance Model (TAM) approach and to examine its contribution to good governance. This research uses a qualitative approach with a descriptive qualitative method. Data were collected through semi-structured interviews, observation, and documentation. Informants were selected purposively based on their knowledge, experience, and involvement in Coretax implementation. Data analysis consisted of data condensation, data display, and conclusion drawing and verification. Data validity was examined through source triangulation, technique triangulation, and member checking. The findings indicate that Coretax implementation supports tax administration by integrating tax reporting and payment processes, improving transparency, facilitating transaction monitoring, and supporting accountability in tax administration. Based on the Perceived Usefulness dimension, Coretax is perceived as beneficial in supporting administrative effectiveness and efficiency. Based on Perceived Ease of Use, users have been able to adapt to and operate the system, although technical obstacles and the need for further training remain. Based on Actual System Use, Coretax has been used as the main system for tax administration. Nevertheless, system errors, data mismatches, slow access, and system instability remain challenges. Overall, Coretax implementation contributes to supporting good governance principles, particularly transparency and accountability, but its implementation still requires continuous system improvement, user readiness, and organizational support..